STRATEGIC MANAGEMENT IN ANTI-CRISIS MANAGEMENT (Development Service Industry Management, 2024)
A person creates, organizes and manages the artificial system of socio-economic purpose, which includes the enterprise. The complexity of socio-economic processes is increasing, and therefore, the task of strategic management, as the basis of the management subsystem of the organization, is to maintain stability on the way to development. The future of the organization depends on the quality of strategic management, which means people in various social and professional roles. Their viability, efficiency and competitiveness depend on the ability of system management to direct organizations to achieve strategic targets, maintain stability and build potential for development. In conditions of rapid changes in the external environment, untimely, unsystematic reaction - strategic management promotes the development of processes of systemic factorization and disintegration in the internal environment of the organization. From the completeness, reliability, and timeliness of information based on which decisions are made/or a management vacuum is formed, the strategic management of the organization contributes to the creation of conditions for the formation of a systemic crisis and its further spread, activation of the mode of problem generation and the onset of a systemic catastrophe, the basis of which is the uncontrolled growth of entropy. Systemic crises and disasters also happen to businesses, for example in the form of bankruptcy, liquidation, etc., and can have long-term consequences for all stakeholders. Separate reformation, in such a situation, can accelerate the processes of disintegration and self-destruction of the system. Overcoming negative consequences can take years, or even decades, depending on the scale of the system. Insufficient development of theoretical and practical work on the creation of prerequisites for the emergence of a systemic crisis, the activation of the problem generation regime, and, as a result, the onset of an anthropogenic systemic disaster, with subsequent reflection on the development of systematic and balanced policies, programs, plans to overcome the consequences, necessary changes and transformations - makes it impossible to break the loop system reinforcing feedback: strategic management that does not meet the challenges - problem generation mode - system crisis - anthropogenic system catastrophe. This article is devoted to these issues with the aim of further methodological development to prevent such systemic problems and disasters in the future.
Keywords: system management; system crisis; systemic catastrophe based on entropy; problem generation mode; enterprise; organization